The diffusion of "green'' buildings in the housing market: empirics on the long run effects of energy efficiency regulation - Claus Michelsen; Makram El-Shagi; Sebastian Rosenschon (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
The impact of environmental regulation on market diffusion and market entry of "green'', innovative buildings in the housing market is studied using a unique data set of German residential buildings. Particularly, we analyze how energy efficiency regulation, in terms of minimum standards, affects energy-requirements in newly constructed buildings over time in both, the high and low quality housing segment. The data we use consists of a large sample of German apartment houses built between 1950 and 2005. We develop a new measure for regulation intensity and apply a panel-error-correction regression model to energy requirements of low and high quality housing. Our findings suggest that regulation is effective and significantly impacts technology adoption in low quality housing. Moreover, we find that regulation indirectly also positively affects energy efficiency in the high quality housing markets. This suggests that tighter building codes have a substantial impact on both, the entry and the diffusion of ``green'' buildings in the housing market.
Keywords: D20; Q40; R30; 330